2008
DOI: 10.1007/s11858-008-0103-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of the researcher’s epistemology in mathematics education: an essay on the case of proof

Abstract: Is there a shared meaning of ''mathematical proof'' among researchers in mathematics education? Almost all researchers may agree on a formal definition of mathematical proof. But beyond this minimal agreement, what is the state of our field? After three decades of activity in this area, being familiar with the most influential pieces of work, I realize that the sharing of keywords hides important differences in the understanding. These differences could be obstacles to scientific progress in this area, if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 7 publications
0
15
0
7
Order By: Relevance
“…Nonetheless, because a narrative model is a living thing, this model of MR will surely evolve and grow in the hands of its users. Lastly, in the spirit of Balacheff (2008), the explicit formulation of the epistemological underpinnings of this model of MR can also be seen as a first step in eventually creating bridges between different epistemologies.…”
Section: A Model Of Mathematical Reasoning For School Mathematicsmentioning
confidence: 99%
“…Nonetheless, because a narrative model is a living thing, this model of MR will surely evolve and grow in the hands of its users. Lastly, in the spirit of Balacheff (2008), the explicit formulation of the epistemological underpinnings of this model of MR can also be seen as a first step in eventually creating bridges between different epistemologies.…”
Section: A Model Of Mathematical Reasoning For School Mathematicsmentioning
confidence: 99%
“…One recommendation is the need for more explicit teaching of proof, both in school and university (Balacheff 2008;Hanna and de Villiers 2008;Hemmi 2008), with some (e.g., Stylianides and Stylianides 2007;Hanna and Barbeau 2008) arguing for it to be made a central topic in both institutions. A possible introduction to proof, suggested by Harel (2008) and Palla et al (2012) is proof by mathematical induction.…”
Section: Proof and Provingmentioning
confidence: 99%
“…They indicate one factor which influences which conception students adopt at any given time. Balacheff (2008) suggested that proof has several different meanings in the mathematics education literature, and pointed out that this could be a hindrance for research progress. The same point may be true for individual students and their mathematical progress.…”
Section: Discussionmentioning
confidence: 99%